2015
DOI: 10.1021/acsami.5b00827
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Impact of Molecular Packing and Device Architecture on the Performance of Nanostructured Perylene Diimide Solar Cells

Abstract: PSS electrode, thus impeding the efficient charge extraction and limiting device photocurrent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 52 publications
(120 reference statements)
3
33
0
Order By: Relevance
“…Excimer states have been observed in other NFAs [ 37,64,66 ] and act as low‐energy trap states that inhibit charge separation of bound electron–hole pairs at the donor–acceptor interface, reducing mobilities and PCEs. [ 36,67–70 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excimer states have been observed in other NFAs [ 37,64,66 ] and act as low‐energy trap states that inhibit charge separation of bound electron–hole pairs at the donor–acceptor interface, reducing mobilities and PCEs. [ 36,67–70 ]…”
Section: Resultsmentioning
confidence: 99%
“…Excimer states have been observed in other NFAs [37,64,66] and act as lowenergy trap states that inhibit charge separation of bound electron-hole pairs at the donor-acceptor interface, reducing mobilities and PCEs. [36,[67][68][69][70] Comparing the normalized steadystate blend absorptions to the transient spectra at ≈1 ps at 580 nm reveals a signifi cant (≈40% and ≈50%) yield of free carriers from ultrafast hole transfer in ITzNF4 and ITNF4, respectively (Figure 7A,B). Monitoring the kinetics of 1* A reveals that ≈80% of 1* A decays within ≈500 fs in both the blends and neat acceptors (Figure 7C,D).…”
Section: Femtosecond Transient Absorption Spectroscopymentioning
confidence: 99%
“…77 Further investigations on the local structural order and molecular packing indicated that electronic connectivity between the large domains of PDI 1 reduced the electron mobility and the local disorder of the PDI domains was essential for efficient electron transport. 78,79 From transient absorption pump-probe spectroscopy, Laquai and coworkers illustrated that the charge separation between PDI 1 and PBDTTT-C is strongly eld-dependent. Upon excitation, both the PDI and polymer excitons undergo fast charge transfer on a time scale of several tens of picoseconds.…”
Section: Small-molecule Non-fullerene Acceptorsmentioning
confidence: 99%
“…S3). Since conventional OPV device geometries with bottom PEDOT:PSS hole-collecting electrodes consistently underestimate the performance of PDI-based OPV bulk heterojunctions,41 we have additionally studied the photovoltaic performance of inverted OPV devices with the glass/ITO/ZnO/PIF8BT:PDI/V2O5/Ag device configuration. Following thermal annealing, these devices performed better with an improvement in the order of ~ 40% for Jsc and of ~ 15% for Voc.Further characterization of the inverted OPV PIF8BT:PDI devices was carried out under variable photoexcitation intensity (Iexc) of continuous-wave (cw) laser light at 532 nm.…”
mentioning
confidence: 99%